2014
DOI: 10.1371/journal.pone.0086608
|View full text |Cite
|
Sign up to set email alerts
|

Inducible, Dose-Adjustable and Time-Restricted Reconstitution of Stat1 Deficiency In Vivo

Abstract: Signal transducer and activator of transcription (STAT) 1 is a key player in interferon (IFN) signaling, essential in mediating host defense against viruses and other pathogens. STAT1 levels are tightly regulated and loss- or gain-of-function mutations in mice and men lead to severe diseases. We have generated a doxycycline (dox) -inducible, FLAG-tagged Stat1 expression system in mice lacking endogenous STAT1 (i.e. Stat1ind mice). We show that STAT1 expression depends on the time and dose of dox treatment in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 75 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…The STAT1 signaling is essential to all three types of IFN pathways and therefore plays an important role in immunosurveillance ( Tymoszuk et al , 2014 ). Specifically, IFN-induced STAT1 activation leads to its binding either to the interferon response elements or Gamma-activated sites, further activating the interferon-induced genes ( Leitner et al , 2014 ). Studies in mice with defective STAT1 activation have shown increased tumour incidence attributed to its tumour-suppressive role in breast tumourigenesis ( Levy and Gilliland, 2000 ; Koromilas and Sexl, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The STAT1 signaling is essential to all three types of IFN pathways and therefore plays an important role in immunosurveillance ( Tymoszuk et al , 2014 ). Specifically, IFN-induced STAT1 activation leads to its binding either to the interferon response elements or Gamma-activated sites, further activating the interferon-induced genes ( Leitner et al , 2014 ). Studies in mice with defective STAT1 activation have shown increased tumour incidence attributed to its tumour-suppressive role in breast tumourigenesis ( Levy and Gilliland, 2000 ; Koromilas and Sexl, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the role of STAT1 that was predicted by our model, we tested cytokine gene expression in wild-type and STAT1 knockout BMDMs derived from STAT1-inducible ( Stat1 ind ) mice without doxycycline treatment (43). We found that the amounts of Il6 and Il12b mRNAs were decreased in the STAT1 knockout cells compared to those in the wild-type cells when they were treated under the I 8 R and I 24 R conditions (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…To gather experimental support for this biphasic response, we tested cytokine mRNA production in response to various amounts of STAT1 in experiments with cells from Stat1 ind mice (43). We first demonstrated the incremental induction of STAT1 abundance in BMDMs derived from Stat1 ind mice and pretreated with doxycycline (0, 0.03125, 0.0625, 0.125, 0.25, and 0.5 μg/ml) (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The type III IFNs are involved in multiple downstream signaling cascades that could affect the abundance of nasal flora through the action of antimicrobial peptides, cytokines that alter barrier function and immune cells recruited across the mucosal surface. The effects of type III IFNs are mediated by JAK/STAT signaling, initiated by phosphorylation of STAT1 ( 28 , 29 ). The relative induction of STAT1 and STAT3 phosphorylation in WT and Il28r −/− mutant mice, exposed to influenza virus or phosphate-buffered saline (PBS), were compared, and Ifnar −/− mutant mice were included as a control for the type I IFNs ( Fig.…”
Section: Resultsmentioning
confidence: 99%